Scoring Ibsen: A New Chamber Opera After A Doll's House - Oberhofer, Grace E. (Tufts Archival Research Center, 2015)
“The door slam heard around the world.” On December 21, 1879, the Royal Theater in Copenhagen premiered the play Et dukkehjem (A Doll’s House), by Henrik Ibsen. Little did the theater know that the final door slam of Ibsen’s work would create shockwaves throughout public audiences not only in Europe, but across the globe. A Doll’s House focuses on the Helmers, a seemingly typical family for late 19th-century Europe, and this archetypal structure allows Ibsen to highlight gender issues in a realistic setting. The mother of the household, Nora, battles through a plot filled with secrecy, manipulation, and constant societal constraint. At last, Nora discovers that she must fully break out of the world she has been held to her entire life in order to truly become an individual: she must find her own music. What is then striking about A Doll’s House to me, as a composer, is the idea of music becoming the bird’s gilded cage—of Nora trapped in the strict, structural confines of a musical format. This led me to write a 90-minute opera in three short acts based on A Doll’s House, which uses the structure of an opera as a symbol of Nora’s confines, as well as, ultimately, her freedom. The piece was performed in full on May 1st, 2015, stage directed by Allison Benko and in collaboration with Bare Bodkin Theatre Company and the Tufts Opera Ensemble.